ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PEMBANGUNAN GEDUNG PASAR MARDIKA KOTA AMBON - Welem Meturan; Lenora Leuhery; Henriette Dorothy Titaley (Journal Agregate, 2023)
Occupational Safety and Health (K3) is a science for the aticipacion recognizing,  evaluation and control of hazards that arise in the workplace that can have an impact on the welfare and health of workers. The risk of falling is the highest cause of accidents. The use of adequate safety equipment such as guardrails and helmets, as well as the implementation of security procedures such as non-permanent ladders inspection and scaffolding can reduce the risk of accidents.Data analysis was used to calculate the analysis of health and work application in the project "Construction of Hitu Village Primary Hospital". The techniques in data analysis in this study are validity test, reliability test, analytical descriptive, regression analysis test, coefficient of  Determination test, T - test and F test.The results of the analysis show that safety (X1) and health (X2) had a positive effect on work performance from the test results of multiple linear regression analysis from the correlation table or partial correlation, where safety (X1) obtained a value of r = 0.766 with a significance  0.000 <0.05. Health (X2) obtained a value of r = 0.592 with a significant 0.000 <0.05. For the value of the Summary Regression Model Correlation (R) which simultaneously (together) between the variables Health (X1) and Safety (X2), on Work Performance (Y) is r  = 0.767. Among the two aspects of safety and health on the work performance of the Hitu Village Primary Hospital Construction project, the most dominant influencing test results of the partial is the occupational safety aspect of 0.722 or 72.2%.